2023
DOI: 10.1149/2162-8777/ad0b8d
|View full text |Cite
|
Sign up to set email alerts
|

Insight on Surface Changes Post Chemical Mechanical Polishing (CMP) of the Silicon Substrate by Adding Polyoxyethylene Ether

Xuejie Wang,
Chenwei Wang,
Mengya Zhu
et al.

Abstract: Fatty alcohol polyoxyethylene ether (AEO-9) and isomeric decyl polyoxyethylene ether (XP-70, XP-90) were tested as additives to the slurries aiming at improving surface quality during Si fine chemical mechanical polishing (CMP) in 14 nm ultra-large-scale integration. Based on large particle count, contact angles analyzer, and polishing data, it was revealed that XP-90 exhibits improved dispersibility and hydrophilicity, reducing roughness and defects. Various analytical results on silicon surfaces including X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Specifically, the addition of AEO-9 reduces the surface roughness of wafers by over 60%. In addition to its molecular structure, the activity of a surfactant is also dependent on its hydrophilic-lipophilic balance (HLB) value [24]. In terms of HLB values, PEG > TPEG > OP-9 > AEO-9.…”
Section: The Effect Of Surfactants With Different Functional Groups O...mentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the addition of AEO-9 reduces the surface roughness of wafers by over 60%. In addition to its molecular structure, the activity of a surfactant is also dependent on its hydrophilic-lipophilic balance (HLB) value [24]. In terms of HLB values, PEG > TPEG > OP-9 > AEO-9.…”
Section: The Effect Of Surfactants With Different Functional Groups O...mentioning
confidence: 99%
“…In terms of HLB values, PEG > TPEG > OP-9 > AEO-9. Studies have shown that the lower the HLB value, the greater the likelihood of micelle formation and the higher the surface tension [24,25]. The polishing performance of monocrystalline silicon wafers was affected differently by these.…”
Section: The Effect Of Surfactants With Different Functional Groups O...mentioning
confidence: 99%